Lifestyle construction on Instagram media on consumer behavior of students at the Faculty of Da'wah and Communication - Syarifah Difta Putri irdiana Syarifah; Tengkuu Walisyah (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2024)
ABSTRACT Teenagers' playtime and study time, especially students, are influenced by advances in communication technology, both positively and negatively. Students use social media to communicate with friends, share homework, play games, and/or fill their free time, to do college assignments. This study aims to examine how students of the Islamic Communication and Broadcasting Study Program at UIN Sumatera Utara use Instagram in their daily lives related to the wasteful behavior of students. The method used in the study is qualitative carried out through observation by conducting direct observations, interviews conducted through interaction, and documentation made in references from literature related to the focus of the study. The results of the study indicate that Instagram plays an important role in shaping the lifestyle of consumptive students. Students are often influenced by content that displays a luxurious lifestyle, which encourages them to shop for unnecessary items and try to display an ideal image on social media. This finding is consistent with the theory of social construction which states that social media users can create reality through interaction on the platform. This study highlights the use of Instagram social media which can influence student behavior that tends to be consumptive, although this is not entirely a problem caused by the presence of social media in the current era. Keywords: Social Media, Instagram, Behavior.